CPAP Does Not Reduce Inflammatory Biomarkers in Patients With Coronary Artery Disease and Nonsleepy Obstructive Sleep Apnea: A Randomized Controlled Trial - (:unkn) unknown (OXFORD UNIV PRESS INC, 2017)
Objectives: Obstructive sleep apnea (OSA) and enhanced vascular inflammation coexist in patients with coronary artery disease (CAD). Continuous positive airway pressure (CPAP) is first-line treatment for OSA with daytime sleepiness. This analysis of data from the RICCADSA (Randomized Intervention with CPAP in Coronary Artery Disease and Sleep Apnea) trial investigated the effects of CPAP on inflammatory markers in patients with CAD and nonsleepy OSA. Methods: This single-center, randomized, controlled, open-label trial enrolled consecutive revascularized patients with nonsleepy OSA (apnea-hypopnea index > 15/h; Epworth Sleepiness Scale score < 10). Levels of high-sensitivity C-reactive protein (hs-CRP), interleukin (IL)-6, IL-8, and tumor necrosis factor-alpha (TNF-alpha) were measured in blood samples taken at baseline (median 94 days after revascularization) and after 1 year of follow-up in patients randomized to CPAP or no-CPAP. Results: A total of 220 patients with analyzable blood samples at baseline and 1 year were included. Baseline IL-6 levels were significantly lower in the CPAP versus no-CPAP group (median 3.1 pmol/L [interquartile range 1.3-5.7] vs. 4.2 pmol/L [2.0-8.9], respectively; p = .005). At 1-year follow-up, median IL-6 levels were significantly reduced in both groups (to 2.2 pmol/L [1.2-3.9] in the CPAP group and to 2.2 [1.2-4.7] in no-CPAP group; both p < .001 vs. baseline). IL-8, hs-CRP, and TNF-a did not change significantly from baseline. There was no association between CPAP adherence and changes in inflammatory marker levels. Conclusions: In patients with stable CAD and nonsleepy OSA, inflammatory biomarkers did not change significantly over time except for IL-6 levels, which reduced to the same extent in the CPAP and no-CPAP groups.
Keywords: continuous positive airway pressure; coronary artery disease; obstructive sleep apnea; interleukin-6; interleukin-8; tumor necrosis factor-alpha; C-REACTIVE PROTEIN; POSITIVE AIRWAY PRESSURE; CARDIOVASCULAR RISK-FACTORS; INTERLEUKIN-6; EVENTS; PREDICTORS; THERAPY; MARKERS